2008
DOI: 10.1080/09540120701867016
|View full text |Cite
|
Sign up to set email alerts
|

Potential markers of female condom use among inner city African-American Women

Abstract: Despite the availability of the female condoms and theoretically based interventions to promote its use, studies have indicated a low level of acceptability of their use among women in most populations. We aimed to determine female condom use prevalence and the potential markers among African-American women. In an intervention trial to test the efficacy of the Information-Motivation-Behavioral Skills model in increasing condom use, we utilized the baseline data of 280 subjects and examined the potential predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…Although women in the intervention group were more likely to insert a female condom 3 and 6 months after the intervention, relatively few women attempted to use it with a partner. The female condom has been found to have variable acceptability in the United States (Hirky et al 2003; Holmes et al 2008; Klein et al 1999; Sly et al 1997; Witte et al 1999), and there are a number of issues that may make it challenging for this population. Women with medication side-effects that include tremors or other movement disorders may find insertion of the female condom difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although women in the intervention group were more likely to insert a female condom 3 and 6 months after the intervention, relatively few women attempted to use it with a partner. The female condom has been found to have variable acceptability in the United States (Hirky et al 2003; Holmes et al 2008; Klein et al 1999; Sly et al 1997; Witte et al 1999), and there are a number of issues that may make it challenging for this population. Women with medication side-effects that include tremors or other movement disorders may find insertion of the female condom difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors increasing use were active drug use, living with someone abusing substances, and having discussed the devise with other women or a regular sex partner (Witte et al 1999). Holmes et al (2008) showed that African American women without knowledge of the female condom were less likely to use it, but that women with multiple partners, high school education or more, and younger age, were more likely to use it. Qualitative and quantitative studies of women at high risk report that women liked the idea of perceived personal control and increased sexual pleasure for women and men associated with female condom use (Hirky et al 2003; Klein et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Holmes et al (2008) in Houston, Texas, among African-American women revealed that the significant potential markers for female condom use were age, multiple sexual relationships, knowledge of the method, and educational status. Women who had multiple sexual relationships were five times more likely to use the female condom than women in monogamous relationships were.…”
Section: Introductionmentioning
confidence: 98%
“…The method's higher cost may also underpin many challenges in female condom promotion. [6][7][8][9][10][11] A post-marketing survey in Zimbabwe in 1998 highlighted the key role of healthcare providers and lay educators in increasing women's access to the female condom. 12 In a study conducted in 1996, preliminary data showed that the female condom was an acceptable method for some Kenyan couples, but the authors noted the necessity of further research on safety, cost-effectiveness, and obstacles to acceptance.…”
Section: Introductionmentioning
confidence: 99%